Workplace Bullying in India : Acts, Consequences, and Control - Misra, Rajnish Kumar; Sharma, Divya (Prabandhan: Indian Journal of Management, 2022)
The purpose of this study was to examine the acts and consequences from the perspective of all actors involved in workplace bullying and to provide suggestions to deal with this threat. A qualitative method was used to gather commentary from public and private sector management teachers as the topic is sensitive, complex, or dilemmatic and focused on describing or understanding the experiences of an individual. A deductive approach to thematic analysis revealed the various acts and consequences from the perspectives of all the parties, that is, perpetrator, victim, bystander, and witness, under one roof that has not been stated in the literature. Furthermore, if organizations follow the suggestions provided in the study to control workplace bullying, that will lead to a better and healthy working environment. The present study contributes to workplace bullying literature by using thematic analysis to explore the acts and consequences of workplace bullying faced by all parties. To strengthen the organization with a better work environment and committed people, this critical issue of bullying should be addressed with utmost priority. If it is addressed early, the treatment becomes easier as prevention is always better than cure.